1998
DOI: 10.1002/bbpc.19981021211
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Birch reduction

Abstract: Because of contradictions in the literature, we reinvestigated the kinetics of the Birch reduction, i.e. the hydrogenation of benzene and its derivatives in metal ammonia solutions (MAS: containing solvated electrons e− and metal cations M+) with alcohols to yield the corresponding cyclohexa‐1,4‐dien compounds (e.g. 2 Li+2CH3OH+C6H6⟹2CH3OLi+C6H8). The kinetics of this reaction are obscured since the hydrogen reaction proceeds parallel to it (2Li+2CH3OH⟹2CH3OLi+H2). The two reactions differ in their activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Pekker et al [17] and Tang et al [5] have also reported that the decomposition of covalent hydrogen functionalized to multiple-walled carbon nanotubes takes place in the range of 400-600°C. Pekker et al [18] detected the effluent hydrogen and methane via a mass spectrometer in this temperature range. At the temperature 400-600°C, the weight loss percent of hydrogenated graphene is much more than that of graphene.…”
Section: Estimation Of Extent Of Hydrogen Storage From Thermogravimetmentioning
confidence: 99%
See 4 more Smart Citations
“…Pekker et al [17] and Tang et al [5] have also reported that the decomposition of covalent hydrogen functionalized to multiple-walled carbon nanotubes takes place in the range of 400-600°C. Pekker et al [18] detected the effluent hydrogen and methane via a mass spectrometer in this temperature range. At the temperature 400-600°C, the weight loss percent of hydrogenated graphene is much more than that of graphene.…”
Section: Estimation Of Extent Of Hydrogen Storage From Thermogravimetmentioning
confidence: 99%
“…Cheng et al [1] reported that at room temperature and 6 Mpa pressure, hydrogen absorption of graphene was less than 0.2 wt.%, whereas hydrogen uptake was 0.4 wt.% at 77 K temperature and 100 kPa. In order to chemically adsorb hydrogen, different methods have been implemented to hydrogenate the graphene including Birch reaction [17,18], high pressure hydrogenation [14,19], H-plasma procedure [20,21], and polyamine hydrogenation [5,9]. Wenhui yuan et al [14] showed that hydrogen absorption was about 2.7 wt.% at 298 K and 25 bars on glucose.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations